Required leadership style and characteristic to achieve the high income economy : the case of ICT (Information Communication and Telecommunication) industry in Malaysia: a review of literature - Baroto, Mas Bambang (2012)
A leadership style is a leader's style of providing direction, implementing plans, and motivating people. Various authors have proposed identifying many different leadership styles as exhibited by leaders in the political, business or other fields.